Gender issues and human rights - Otto, Dianne (Cheltenham, UK : Edward Elgar, 2013)
'The 1990s witnessed a surge of feminist human rights scholarship and activism in international law which has shaped jurisprudential and institutional developments, yet gender issues and human rights still remains a topical and evolving field of study. In this collection, Professor Otto brings together seminal works which are united in their aim of challenging the existing gendered hierarchies of power, inequality and those natural foundations that have justified oppressive gender stereotypes. Included works cover, among others, the history and early developments of women's rights, structural critiques of international human rights law, recognizing new human rights, linking women's needs and human rights and thinking beyond the duality of gender'--Back cover.
Includes bibliographical references (pages vii-viii).
Keywords: Women (International law); Women's rights